Imaging fibrin formation and platelet and endothelial cell activation in vivo - Bellido-Martin, Lola; Chen, Vivien; Jasuja, Reema; Furie, Bruce; Furie, Barbara C. (Thrombosis and Haemostasis, 2011)
Over the past six decades research employing in vitro assays has identified enzymes, cofactors, cell receptors and associated ligands important to the haemostatic process and its regulation. These studies have greatly advanced our understanding of the molecular and cellular bases of haemostasis and thrombosis. However, in vitro assays cannot simultaneously reproduce the interactions of all of the components of the haemostatic process that occur in vivo nor do they reflect the importance of haemodynamic factors resulting from blood flow. To overcome these limitations investigators have increasingly turned to animal models of haemostasis and thrombosis. In this article we describe some advances in the visualisation of platelet and endothelial cell activation and blood coagulation in vivo and review what we have learned from our intravital microscopy experiments using primarily the laser-induced injury model for thrombosis.
Keywords: Animal models; thrombosis; intravital imaging